1994
DOI: 10.1002/gcc.2870090111
|View full text |Cite
|
Sign up to set email alerts
|

Localization of amplified MYC gene sequences to double minute chromosomes in acute myelogenous leukemia

Abstract: Cytogenetic and molecular studies were performed on two dmin-bearing acute myelogenous leukemia (FAB-M2) samples. Both cases were characterized by complex karyotypes containing interstitial deletions of the long arm of chromosome 8 altering band 8q24.1, aberrations affecting the short arm of chromosome 17, and multiple double minute chromosomes (dmin). Using a 1.4 kb cDNA probe coding for the third exon of the MYC oncogene, DNA slot blots indicated MYC gene sequences were amplified in both samples. Fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…However a number of reports, all consisting of individual or small numbers of patients, have reported C-MYC ampli®cation in association with DMs Asker et al, 1988;Fugazza et al, 1997;Tanaka et al, 1993;Slovak et al, 1994;Karasawa et al, 1996;Mohamed et al, 1996;Reddy and Sulcova, 1997;Jennings and Mills, 1998). Because of the limited sizes of each study and institutional variability in management, the prognostic value of these ®ndings remains uncertain.…”
Section: Myeloid Leukemiamentioning
confidence: 99%
“…However a number of reports, all consisting of individual or small numbers of patients, have reported C-MYC ampli®cation in association with DMs Asker et al, 1988;Fugazza et al, 1997;Tanaka et al, 1993;Slovak et al, 1994;Karasawa et al, 1996;Mohamed et al, 1996;Reddy and Sulcova, 1997;Jennings and Mills, 1998). Because of the limited sizes of each study and institutional variability in management, the prognostic value of these ®ndings remains uncertain.…”
Section: Myeloid Leukemiamentioning
confidence: 99%
“…The proto-oncogene c-MYC encodes a basic helix-loop-helix leucine zipper transcription factor that, dimerizing with its partner MAX, controls multiple cell functions. Patients with myeloid leukemias are often characterized by the presence of double minute chromosomes that contain MYC amplification (19,20), and a recent study suggests that several oncogenes, involved in myeloid tumor progression, induce leukemogenesis by activating c-MYC oncoprotein (21). Moreover, in CML, some studies have shown that BCR-ABL can indirectly activate c-MYC function via either the Janus-activated kinase (JAK2) pathway (22) or the mitogen-activated protein kinase/heterogeneous nuclear ribonucleoprotein K (MAPK/HNRPK) pathway (23) causing increased c-MYC mRNA translation.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid clinical deterioration of our patient, who died after 8 months, agrees well with several previous reports stating that dmin in general, as well as MYC-containing dmin, is associated with a short survival. 2 However, this has been questioned recently by Bruckert et al, 3 who, in a review of 11 AML with dmin harboring MYC, concluded that dmin may not confer a poor prognosis unless associated with a complex karyotype. In line with this, the CMML patient reported by Sambani et al 6 survived more than 20 months.…”
mentioning
confidence: 99%
“…1 In these diseases, dmin appear to be more frequent in myeloid malignancies, especially AML, 1 and may be associated with a poor prognosis. 2,3 Most cases display additional chromosomal aberrations; the few cases reported to date with dmin as a sole abnormality have, with one exception, all been AML. 1 Molecular genetic investigations of dmin in hematologic malignancies have revealed that the vast majority contains amplified sequences derived from chromosome band 8q24, including the MYC oncogene, but dmin harboring MLL have also been reported as well as some with amplification of none of these genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation